The Role of the Sembalun Community Development Center in Increasing Ecological Awareness and Economic Development of the Sembalun Village Community - Latifah Handayani; Yahya Himni, M Saleh (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2023)
Humans, nature, animals and plants are one unit that forms the cycle of life. These four elements are the conditions for balance for the survival of life. If one of them is disturbed, the other elements will also be shaken. The ongoing environmental problems are also caused by the very worrying economic conditions of society. As a result of poverty, nature is the only object that is seen as capable of liberating itself from the many economic problems that are increasingly entangling life. If so, then balancing nature for the lives of the next generation is no longer unthinkable. The increasingly brutal behavior of society causes various kinds of life problems to increasingly emerge. Therefore, in this research, researchers will discuss ecological awareness and economic development carried out by social institutions, namely the Sembalun Community Development Center, which is located on the island of Lombok, precisely in Sembalun village, a village around the slopes of Mount Rinjani. The method used in this research is a qualitative method, descriptive analysis. In this research, it can be seen that SCDC plays an important role in maintaining natural balance and the socio-economic welfare of the community.